Service providers' experiences of using a telehealth network 12 months after digitisation of a large Australian rural mental health service. (October 2016) - Newman, Lareen; Bidargaddi, Niranjan; Schrader, Geoffrey
Highlights: We evaluate the digitised version of a statewide telehealth system for mental health care provision to rural and remote areas. We examine service provider experiences of using the telehealth system in the 12 months after the digitisation. Telehealth uptake by psychiatrists, GPs and hospital staff for mental health care in rural and remote areas will increase if technical, administrative, financial, time and cultural factors are addressed. Health service provider input to telehealth system design could reduce barriers to uptake and increase positive telehealth experiences to contribute to ongoing use. Abstract: Background: Despite evidence of benefits of telehealth networks in increasing access to, or providing, previously unavailable mental health services, care providers still prefer traditional approaches. For psychiatric assessment, digital technology can offer improvements over analog systems for the technical and, subsequently, the social quality of provider-client interaction. This is in turn expected to support greater provider uptake and enhanced patient benefits. Objective: Within the framework of Innovation Diffusion Theory, to study service providers' experiences of an existing regional telehealth network for mental health care practice twelve months after digitisation in order to identify the benefits of digital telehealth over an analog system for mental health care purposes in rural Australia. Methods: Qualitative interviews and focus groups were conducted with over 40 service providers from June to September 2013 in South Australia, ranging from the metropolitan central operations to health providers located up to 600 km away in rural and remote areas of the same state. Participants included rural mental health teams, directors of nursing at rural hospitals, metropolitan-based psychiatrists and registrars, the metropolitan-based mental health team dedicated to rural provider support, rural GPs, administrative staff, and the executive group of the state rural health department. Fieldwork was conducted 12 months after the analog system was digitised. The interview and focus group data were analysed using thematic analysis, focusing on three key areas of innovation diffusion theory: relative advantage, technical complexity and technical compatibility. Results: Five themes with 11 sub-themes were identified: (1) "Existing Uses", with three sub-themes: current mental health use, use by GPs, and use for staff support; (2) "Relative Advantage", with four sub-themes: improved technical quality, improved clinical practice, time and cost benefits for providers, and improved patient care; (3) "Technical Complexity"; (4) "Technical Compatibility" with two sub-themes: technical-clinical and technical-administrative; and (5) "Broader Organisational Culture", with two sub-themes: organizational policy support and 'digital telehealth' culture. Conclusions: The digitised telehealth network was generally well received by providers and adopted into clinical practice. Compared with the previous analog system, staff found advantages in better visual and audio quality, more technical stability with less "drop-out", less time delay to conversations and less confusion for clients. Despite these advantages, providers identified a range of challenges to starting or continuing use and they recommended improvements to increase uptake among mental health service providers and other providers (including GPs), and to clinical uses other than mental health. To further increase uptake and impact of telehealth-mediated mental health care in rural and remote areas, even with a high quality digital system, future research must design innovative care models, consider time and cost incentives for providers to use telehealth, and must focus not only on technical training but also how to best integrate technology with clinical practice and must develop an organization-wide digital telehealth culture.